EFEKTIVITAS PERAN UU ITE DALAM RANGKA MELINDUNGI SERTA MENJAGA SELURUH AKTIVITAS SIBER YANG ADA DI INDONESIA - Pan Dhadha, Tegar; Rahayu, Laras Atika; Resmi, Dewi Sito; Kusumastuti, Dora (Universitas Muhammadiyah Ponorogo, 2022)
The issuance of Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) made Indonesian law enter a new phase. The existence of the ITE Law is intended to answer all legal issues that are often faced in the cyber world related to the delivery of information, communication, and / or transactions electronically. This law is also expected to be able to regulate all matters in the cyber world. As a pioneer of cyber law in Indonesia, the ITE Law still has various shortcomings in its implementation. So that effectiveness in protecting cyber activities in Indonesia has not been achieved. However, to achieve the objectives of the ITE Law to be effective and efficient, there needs to be cooperation between the community and the government. This synergy will eventually be able to realize the complete principle of checks and balances. After all, the implementation of the law in the empirical aspect must be guarded so that the spirit of the law itself can be preserved.